The genome sequence of the Brindled Beauty, Lycia hirtaria (Clerck, 1759) [version 1; peer review: 3 approved] - Douglas Boyes; Peter W.H. Holland (Wellcome Open Research, 2023)
We present a genome assembly from an individual male Lycia hirtaria (the Brindled Beauty; Arthropoda; Insecta; Lepidoptera; Geometridae). The genome sequence is 552.0 megabases in span. Most of the assembly is scaffolded into 14 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 15.58 kilobases in length.